Post-traumatic rupture of splenic hydatid cyst: A case report - Kashanizadeh, Atefeh; Daniali, Maziar; Motaghi, Paniz (Indian Journal of Case Reports, 2019)
The worldwide incidence of splenic hydatid cysts is 0.5-4% with Iran holding the distinction of having the most incidence among cattle-rearing areas. About 30% of hydatid cysts of the spleen are asymptomatic and remain undiagnosed unless they rupture spontaneously. In general, rupture of a hydatid cyst secondary to trauma is a very rare condition. Here, we are presenting the case of a19-year-old male with a diagnosis of splenic hydatid cyst rupture secondary to multiple trauma due to falling from a height of 10 meters. In the current case, we discuss the diagnosis and surgical management of a rare presentation of ruptured hydatid cyst. Diagnosis of splenic hydatid cyst was not made before he underwent laparotomy. At operation, we found a ruptured hydatid cyst and performed splenectomy with complete excision of the cyst and its germinal layer.